Unravelling causes of defects in construction. Issue 2 (7th April 2015) - Jingmond, Monika; Ågren, Robert
Abstract : Purpose: – The purpose of this study is to identify the primary root causes of defects in terms of why they persist in construction, despite the increasing implementation of quality systems. Defects in construction continue to be a source of concern in the construction industry. There have been studies that have tried to identify causes of defects. Although concepts are usually related to organisational factors, previous studies have been carried out on an operational level. There is a well-trodden area within the literature relating to the operational level, but little is known about the causes of defects on a higher, organisational level within construction. Design/methodology/approach: – A new approach based on the notion of process causality and the use of cognitive mapping has been adopted. The aim was to take a step back and unravel causes of defects in the execution of construction projects. From workshops with representatives drawn from different parts of the industry, themes have been identified and investigated from a causation perspective. Findings: – It was found that the causes of defects mainly reside in endogenous factors within organisations as opposed to execution failure or exogenous factors related to market, material or equipment behaviour. Originality/value: – More specifically, it was found that the dominant cause of defects lies within organisational shortcomings, suggesting that improvements can be found on the management and strategic levels within projects instead of on the operational level.